Algae in acid mine drainage and relationships with pollutants in a degraded mining ecosystem - Gomes, Patrícia (2021)
Acid mine drainage represents an extreme environment with high concentrations of potentially toxic elements and low pH values. These aquatic habitats are characterised by harsh conditions for biota, being dominated by acidophilic organisms. The study site, São Domingos mine, located in one of the largest metallogenetic provinces in the world, the Iberian Pyrite Belt, was closed without preventive measures. To identify the algae species and understand the relationships with abiotic parameters of the ecosystem, water and biological material were collected and analysed. Digital terrain models were obtained with an unmanned aerial vehicle for geomorphological and hydrologic characterisation of the mine degraded landscape. The results show two types of algal colours that seem to represent different degrees of photosynthetic activity. Optical and scanning electron microscopy revealed 14 taxa at the genus level, divided into eight classes. The genus Mougeotia is the most abundant multicellular algae. With respect to unicellular algae, diatoms are ubiquitous and abundant. Abiotic analyses expose typical features of acid mine drainage and support an inverse relationship between chemical contamination and biological diversity. Factorial correspondence analysis indicates three groups of attributes and samples by their relationship with specific toxic elements. This analysis also suggests a close association between Spirogyra and Pb, together composing a structurally simple ecosystem. The highest contamination in the river system is related to the hydrologic patterns obtained from photogrammetric products, such as the digital surface model and flow map accumulation, indicating the input of leachates from the section having the finest sulfide-rich wastes. Information about the algae community and their association with flow patterns of toxic elements is a relevant tool from a biomonitoring perspective.